East and West: global challenges to achieving carbon neutrality - S. S. Belikova; A. V. Belikov (Управление)
The aim of the study is to determine the factors of occurrence and reasons for growth of the energy crisis in the context of the transition to carbon and climate neutrality of European Union’s countries, People’s Republic of China. The energy problems that have arisen in the economy on the way to reducing the indicators of anthropogenic impact on climate change and provoked the energy crisis of the 2021 second half and is currently ongoing in the European Union countries and China were analysed. The main objective of the research is to study the mechanism of cross-border carbon regulation aimed at protecting European producers from environmental dumping and designed to reduce the risks of migration of carbon-intensive industries to countries with a less stringent climate policy. The relevance of the research topic is due to the need to identify steps to modernise the energy sector of the economies of countries that are just embarking on the path of carbon neutrality in order to prevent such energy crises. The results of the study can be used in the formation and adaptation of energy transition strategies for all states and subnational associations that have attempted to achieve carbon neutrality. When reviewing and correcting climate initiatives, a strategy to form a reserve of reliable and cost-effective basic generating capacities has been proposed.